2018
DOI: 10.1080/02770903.2018.1424185
|View full text |Cite
|
Sign up to set email alerts
|

Educational and home-environment asthma interventions for children in urban, low-income, minority families

Abstract: Results indicated many of the environmental change and education interventions improved asthma management and some symptoms. A multipronged approach may be a good method for targeting both education and change in the home and school environment to promote the well-being of young children in urban areas. New research with careful documentation of information about study participants, dose of intervention (i.e., number and duration of sessions, booster sessions) and specific intervention components also will pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The increased risk for asthma and related hospitalizations among public housing residents has been the focus of many public health and primary care efforts but remains persistent among youth in public housing. 25 - 27 The increase in obesity with age in our study mirrors population trends and shows that the disparity begins in early childhood. Given that a larger proportion of youth in federally assisted housing attend well visits than the general population (84% vs 77%), these results highlight a potential window for more targeted interventions to reach youth in public housing while they are still engaged in primary care.…”
Section: Discussionsupporting
confidence: 72%
“…The increased risk for asthma and related hospitalizations among public housing residents has been the focus of many public health and primary care efforts but remains persistent among youth in public housing. 25 - 27 The increase in obesity with age in our study mirrors population trends and shows that the disparity begins in early childhood. Given that a larger proportion of youth in federally assisted housing attend well visits than the general population (84% vs 77%), these results highlight a potential window for more targeted interventions to reach youth in public housing while they are still engaged in primary care.…”
Section: Discussionsupporting
confidence: 72%
“… 7 Another review of 12 studies of school-based educational programs, including both in-person and computerized interventions and focusing specifically on low-income, minority populations, found many to be effective in improving patient-reported asthma outcomes, self-management, and health care utilization. 6 Our findings indicating improvement in the AIRS-SR postintervention confirms the conclusions of previous studies, supporting the relationship between improved asthma knowledge and improved outcomes and decreased health care utilization.…”
Section: Discussionsupporting
confidence: 90%
“… 4 Asthma management guidelines are linked to reductions in asthma morbidity, focusing on patient education, monitoring asthma symptoms, and optimizing medications and adherence. 5 , 6 , 7 , 8 , 9 However, outpatient settings face critical time constraints and other barriers to the delivery of guideline-based asthma care. One survey of practitioners found that only approximately 5% utilize asthma action plans for their patients, whereas another found few patients used asthma action plans at the initiation of their study.…”
Section: Introductionmentioning
confidence: 99%
“…Such interventions may need to expand their focus to be more inclusive of children with asthma. Information gleaned from the child may also help guide necessary community interventions such as improvements in housing (Welker, Nabors, Lang, & Bernstein, 2018). This is particularly important in attempting to mitigate and reduce health disparities among diverse and historically disenfranchised populations.…”
Section: Relevance To Nursing Practice Education or Researchmentioning
confidence: 99%